Relationships between body composition and anaerobic performance parameters in female handball players - Kale, M.; Akdogan, E. (Physical Education of Students, 2020)
Background and Study Aim. The purpose of this study was to investigate of the relationships between total/segmental body composition and anaerobic performance parameters in female handball players. Material and Methods. Voluntary 16 women handball players (age= 19.6±2.6years, body height= 168.0±5.5cm, body weight= 64.7±10.7kg), trained last 3 years, were participated to the study. Twelve of them were students from Faculty of Sports Sciences. All measurement and tests were completed in the week right after Turkish Women Handball 1th League. Total and segmental body composition parameters (body fat percentage, body fat mass, lean body mass, leg fat percentage, leg fat mass, lean leg mass, torso fat percentage, torso fat mass, and lean torso mass) of each player were evaluated with dual-energy X-ray absorptiometry method. Squat jump test for explosive power, countermovement jump test for elastic (reactive) power, and Wingate test for anaerobic power (WAnT AP) and anaerobic capacity (WAnT AC) were used. Relationships of total/segmental body composition parameters with jump and anaerobic power-capacity parameters were analysed with Pearson correlation and the probability level was set to p£0.05. Results. As a result of statistical analyses, there were negative relationships (p<0.05) between anaerobic performance parameters (countermovement jump and anaerobic power-capacity) and total/segmental body composition parameters except for lean body mass, lean leg mass, and lean torso mass. Conclusions. Total/segmental body composition parameters based on endomorphy had negative effects on explosive power, elastic power, WAnT AP and WAnT AC. It is suggested that coaches should not allow female handball players to rise in ectomorphy for the anaerobic performance loss in the season finale.